Does aid cause changes in economic freedom?. (16th June 2022) - Pavlik, Jamie Bologna; Powell, Benjamin; Young, Andrew T.
Abstract: We examine whether aid affects recipient countries' economic freedom. The existing empirical literature examining this relationship has found conflicting results. However, all of these existing studies have struggled to employ plausible identification strategies to find a causal relationship between aid and economic freedom. Our study employs matching methods to better estimate the causal relationship between aid and economic freedom. We find that there is no meaningful causal impact of overall aid on recipient countries' economic freedom. There is some evidence that, specifically, large and sustained increases in "governance‐specific" aid lead to increases in economic freedom, but even then the effects appear to be quantitatively modest.